MANAGEMENT OF RUPTURED AMOEBIC LIVER ABSCESS: 22-YEARS EXPERIENCE - Memon, AS; Siddiqui, FG; Memon, HA; Ali, SA (Journal of Ayub Medical College Abbottabad, 2010)
Background: Amoebiasis affects approximately 10% of the population all over the world. Amoebic liver abscess (ALA) is the commonest complication of amoebiasis affecting 3-9% victims. It is an ancient disease as Hippocrates notified large hepatic abscesses likely to be amoebic abscesses. Objective of this study was to see the efficacy of conservative treatment in the management of ruptured amoebic liver abscess. Methods: Record of 1,083 patients of amoebic liver abscess, who were treated and managed at Liaquat University Hospital between January 1986 and December 2007, was reviewed retrospectively. Amongst these, 36 (3.32%) patients, found to have intra-peritoneal rupture of the liver abscess were included in this study. The record of these patients was reviewed. The patients were divided into group A and B depending upon the mode of treatment employed. Group A included 16 (44.44%) patients in whom exploratory laparotomy was performed while group B included 20 (55.55%) patients who were treated conservatively. Results: Group A consisted of 16 (44.4%) patients who underwent laparotomy for acute peritonitis due to non-availability of ultrasound in the initial period of the study. In group B, all twenty patients were treated conservatively after a diagnosis of ruptured amoebic liver abscess made by ultrasound guided percutaneous aspiration of pus. These patients were treated with ultrasound guided aspiration of pus with placement of peritoneal drain under local anaesthesia. Six patients in group A died compared to one patient in group B. the overall mortality of ruptured amoebic liver abscess was 19.4%. It was higher in patients treated surgically (37.5%) compared to patients who were treated conservatively (5%). Conclusion: Conservative treatment is an effective modality of treatment for ruptured liver abscess with minimum mortality and mortality if diagnosis is made early. Keywords: Amoebic liver abscess, intra-peritoneal rupture, exploratory laparotomy, conservative treatment, mortality and morbidity